Novel surgical procedure for preventing anastomotic leakage following colorectal cancer surgery: A propensity score matching study - Tang, Gang; Pi, Feng; Zhang, Da-Hong; Qiu, Yu-Hao; Wei, Zheng-Qiang (Frontiers in Oncology, 2022)
Hypoperfusion is the main cause of anastomotic leakage (AL) following colorectal surgery. The conventional method for evaluating anastomotic perfusion is to observe color change and active bleeding of the resection margin of the intestine and the pulsation of mesenteric vessels. However, the accuracy of this method is low, which may be due to insufficient observation time. A novel surgical procedure that separates the mesentery in advance at the intended transection site can delay the observation of anastomotic perfusion, and can potentially detect more anastomotic sites with insufficient vascular supply and reduce the rate of AL. This study aimed to investigate the effects of a novel surgical procedure on AL following sigmoid colon and rectal cancer surgeries. A total of 343 patients who underwent rectal and sigmoid colon cancer surgeries were included in the study. From August 2021 to June 2022, patients with sigmoid colon or rectal cancer underwent a new surgical procedure of pre-division of the mesentery (PDM) at the intended transection site (PDM group). Patients with colorectal cancer who underwent conventional surgical procedures from August 2018 to July 2021 were categorized as the non-PDM group. Symptomatic AL (SAL) within 30 days and other outcomes were retrospectively analyzed using propensity score matching and compared between the two groups. The incidences of SAL were 1.3% and 11.3% in the PDM and non-PDM groups, respectively. PDM significantly reduced the SAL rate in sigmoid colon and rectal cancer surgeries (P = 0.009). The incidence of total postoperative complications (P < 0.05) was significantly lower in the PDM group than that in the non-PDM group. There were no significant differences between the two groups for operative time (P = 0.662), intraoperative blood loss (P = 0.651), intraoperative blood transfusion (P = 0.316), and intensive care rate (P = 1). The length of postoperative hospital stay (P = 0.010) and first exhaust (P = 0.001) and defecation time (P < 0.05) were shorter in the PDM group than in the non-PDM group. PDM can effectively prevent AL, and this procedure can be safely performed in sigmoid colon and rectal cancer surgeries.